Research and Development in Educational Management: A Systematic Literature Review - Asrul Jauhari; Naf’an Tatihoran; Rizal Firdaus (Universitas Al-Hikmah Indonesia, 2025)
Research and Development (R&D) in educational management aims to identify, develop, and test innovative methods or products that can improve the quality of education. Through a systematic literature review, this study evaluates previous findings to provide in-depth insights into best practices in educational management. The objective of this research is to identify and analyze the approach of Research and Development (R&D) in educational management through a systematic review. This research aims to evaluate the effectiveness of innovations in educational managerial practices, as well as provide evidence-based recommendations for better policy and strategy development in education. This study uses a systematic review method to examine relevant literature on Research and Development (R&D) in educational management. The approach aims to analyze findings from various previous studies, synthesize information, and identify patterns or trends in the application of R&D in education. The results of this study show that Research and Development (R&D) in educational management plays a crucial role in improving education quality through innovation and system improvement. The main findings reveal that the R&D approach can strengthen educational policies and improve teaching practices by using evidence-based and valid data. In conclusion, Research and Development (R&D) in educational management is an effective approach to improving the quality of education through evidence-based innovation. This study highlights the importance of applying R&D to identify educational issues and develop more efficient and relevant solutions in the field of education.